Corpus-based Online Word Formation Exercises for Advanced Learners of English – Challenges and Solutions - Krynicki, Grzegorz (RAM-Verlag, 2013)
The paper presents the design and operation of an online platform for word formation practice. The system is based on a pre-defined list of pairs of base and derived forms and usage examples drawn automatically from the British National Corpus. A procedure for the extraction of example sentences is outlined. Results of 372 users’ interacting with the system for over 4.5 month are reviewed. The question about what factors influence users’ evaluation of specific exercises as more difficult is addressed. The results may be relevant in the area of language testing, preparation of examination materials, student-teacher online interaction and teaching English word formation.
Keywords: data-driven learning; word formation; language corpora; English; British National Corpus; online learning